Ageing Europe: understanding the challenges and opportunities of living longer in the households energy use - Magalhães, Vera Juliana e Pais de (2022)
The purpose of this doctorate thesis is to consider in depth the link between two of today’s biggest global challenges: a rapidly ageing population and energy consumption. To understand how this change in population structure affects energy consumption in the residential sector, two approaches are provided: (i) Electricity consumption per capita and (ii) Energy consumption per household. The 1st approach uses electricity consumption efficiency of an ageing population. It considers the 28-member states of the European Union for the period between 2005 and 2016, divided into two scientific articles: 1.1) Household Electricity consumption efficiency of an ageing population; and 2.1) Determinants of electricity consumption efficiency for an ageing population. The first article ranks the countries by levels of efficiency. It proposes policy recommendations which consider the best performers (benchmarking) through the employment of the Data Envelopment Analysis (DEA) method. The second article defines the efficiency determinants for electricity consumption per capita of an ageing population through the employment of the Fractional Regression Method (FRM). The main findings suggest that countries with the lowest performance have the highest share of elderly per capita, are the lowest consumers of electricity per capita, have the highest electricity prices, and present the lowest incomes. Countries with the best performance are also the biggest consumers of electricity per capita have the highest share of electricity generated from renewables. The drivers that positively impulse efficiency are Renewables in Heating and Cooling, Government expenditures in housing and community and a Housing cost burden below 60% for people aged 65 and over. The drivers impacting negatively on efficiency are a high Old age dependency ratio and a Housing cost burden above 60%. The per capita analysis showed that for improved performance, policies should account for measures that increase investment in renewable energy sources, deliver broad social housing policies, provide incentives for homeowners, present regulation changes, and offer suitable financial incentives, all through publicity that the elderly can understand. The per capita analysis also confirmed that the lowest performance might also be linked to energy poverty, high expenditure in households and the poor energy performance of buildings. The 2nd approach is based on the consumption of energy per household and is divided into two scientific articles: 2.1) Drivers, lifestyles, and consumption patterns of elderly households; and 2.2) What are the energy poverty drivers for an ageing population? The purpose of the first article is to evaluate the effect of an ageing population on energy use per household by focusing on factors directly linked to elderly households. In this analysis, the panel is also divided into groups of countries that share weather similarities. The analysis is conducted for the panel of European Union countries between 2005 and 2018 through the employment of the Panel Corrected Standard Errors (PCSEs) Model. The second article determines the energy poverty drivers related to an ageing population that influence the efficiency levels of the energy use per household, through the employment of the Stochastic Frontier Analysis (SFA) method, for the panel of the 28 EU members, for the period between 2007 and 2018. Significant differences were found between the panel and groups of countries, suggesting that climate is clearly important for the definition of adjusted measures, especially for the elderly, a group that is more sensitive to temperature differences because of their health and well-being. The main results of the second article show that the Mediterranean countries have the worst performance in the ranking. Energy poverty (EP) among the elderly is predicated on a rise in energy prices, low income, high-energy expenditure, inefficient buildings or appliances and material deprivation. The challenges that arise from the Energy Per household analysis and the ones that are derived from the Electricity Per Capita analysis show the same issues for the elderly, repeatedly: low incomes, increasing income inequalities, rising energy prices which cannot be met by an increase in income, high housing expenditure, an increasing number of one-adult households, a lack of knowledge and information regarding renewable energy options and incentives for saving measures, and the mounting risk of EP prevalence for this type of population due to their history, their lifestyle and their culture. Bearing in mind the challenges that arise from both analyses, this research suggests some recommendations that could represent global solutions for the member states of the EU, namely: Regulation change regarding energy prices, better regulation of the housing market, protection of the elderly with low incomes, support for the replacement of old appliances and increasing housing efficiency, provision of access to renewable energy for the elderly by proposing adjusted financial measures, incentives to homeowners, involving the elderly in the discussion of policy and planning, clear concise and straightforward messages that are specifically tailored for the elderly. Political answers should also account for the right combination between achieving goals at an EU level while meeting the needs of the elderly at a local level.